Light at the end of the tunnel: FRAP assays combined with super resolution microscopy confirm the presence of a tubular vacuole network in meristematic plant cells - Scheuring, David; Minina, Alyona; Krüger, Falco; Lupanga, Upendo; Krebs, Melanie; Schumacher, Karin (The plant cell, 2024)
Plant vacuoles play key roles in cellular homeostasis, performing catabolic and storage functions, and regulating pH and ion balance. Despite their essential role, there is still no consensus on how vacuoles are established. A model proposing that the endoplasmic reticulum is the main contributor of membrane for growing vacuoles in meristematic cells has been challenged by a study proposing that plant vacuoles are formed de novo by homotypic fusion of multivesicular bodies (MVBs). Here, we use the Arabidopsis thaliana root as a model system to provide a systematic overview of successive vacuole biogenesis stages, starting from the youngest cells proximate to the quiescent center. We combine in vivo high- and super-resolution (STED) microscopy to demonstrate the presence of tubular and connected vacuolar structures in all meristematic cells. Using customized fluorescence recovery after photobleaching (FRAP) assays, we establish different modes of connectivity and demonstrate that thin, tubular vacuoles, as observed in cells near the quiescent center, form an interconnected network. Finally, we argue that a growing body of evidence indicates that vacuolar structures cannot originate from MVBs alone but receive membrane material from different sources simultaneously.
Gesehen am 20.03.2025